The Effects of High-Performance Work Practices and Psychological Capital on Hotel Employees’ Outcomes: The Mediating Role of Work Engagement - Karadaş, Georgiana (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
The purpose of this thesis is to develop and test a research model that examines the interrelationships of high-performance work practices, psychological capital, work engagement, quitting intentions, creative performance, and extra-role performance. To serve this purpose, data were collected from customer-contact employees and their immediate supervisors in the international five- and four-star hotels in Romania. Data were obtained from customer-contact employees with a time lag of two weeks in three waves. The results reveal that all hypotheses shown in the research model are supported. Specifically, high-performance work practices, as manifested by selective staffing, job security, training, empowerment, rewards, teamwork, and career opportunities, enhance hotel employees’ psychological capital and work engagement. Psychological capital triggers also work engagement. These results show that psychological capital is a mediator in the abovementioned relationships. In addition, both psychological capital and work engagement foster creative and extra-role performances, while they alleviate employees’ intent to quit. Work engagement is a mediator in the relationships given above. The theoretical and practical contributions to the relevant literature are discussed in light of the study findings and recommendations for future research are given. Keywords: Employee outcomes, High-performance work practices, Psychological capital, Romania, Work engagement

ÖZ: Bu tezin amacı, yüksek performanslı insan kaynakları uygulamaları, psikolojik sermaye, işe angaje olma, işten ayrılma niyeti, yaratıcı performans ve ekstra performans arasındaki ilişkileri inceleyen bir araştırma modelini geliştirip test etmektir. Bu amaca ulaşmak için, Romanya’da uluslararası beş ve dört yıldızlı zincir otel işletmelerindeki sınır birim işgörenleri ve onların bağlı olduğu yöneticilerden veri toplanmıştır. İşgörenlerden veri, üç dalgada iki haftalık zaman aralığında toplanmıştır. Çalışmanın bulguları, araştırma modelinin geçerli olduğunu ve tüm hipotezlerin desteklendiğini göstermiştir. Şöyle ki, dikkatli personel alımı, iş güvenliği, eğitim, güçlendirme, ödüllendirme, takım çalışması ve kariyer olanaklarından oluşan yüksek performanslı insan kaynakları uygulamaları otel çalışanlarının psikolojik sermayesi ile işe angaje olmasını artırmıştır. Psikolojik sermaye, aynı zamanda işe angaje olmayı tetiklemektedir. Burada psikolojik sermaye, aracı rolü oynamaktadır. Bu bulgulara ek olarak, hem psikolojik sermaye hem de işe angaje olma yaratıcı ve ekstra performansı artırırken, otel çalışanlarının işten ayrılma niyetini düşürmektedir. Burada işe angaje olma aracı rolüne sahiptir. Yukarıda verilen bulgular ışığında, bu çalışmanın teorik ve uygulama açısından ilgili yazına katkıları tartışılmış, gelecek araştırmalar için birtakım önerilerde bulunulmuştur. Anahtar Kelimeler: İşe angaje olma, İşgörenin sonuç değişkenleri, Psikolojik sermaye, Romanya, Yüksek performanslı insan kaynakları uygulamaları
Doctor of Philosophy in Tourism Management. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Tourism, 2016. Supervisor: Prof. Dr. Osman M. Karatepe.
Keywords: Tourism; Employee motivation-Psychology, Industrial-Work-Psychological aspects-Employees-Attitudes-Personnel management-Work environment; Employee outcomes; High-performance work practices; Psychological capital; Romania; Work engagement